A nitrogen-doped unzipped carbon nanotube/sulfur composite as an advanced cathode for lithium–sulfur batteries. (14th September 2015) - Chen, Liang; Chen, Zhongxue; Huang, Zheng; Wang, Yingfei; Zhou, Haihui; Kuang, Yafei
Abstract : Rational design of the cathode nanostructure and successful nitrogen doping lead to excellent electrochemical performance of the NUCNT/S cathode. Abstract : In this work, a nitrogen-doped unzipped carbon nanotube/sulfur (NUCNT/S) composite was initially synthesized by a low-cost and scalable process and investigated as a cathode material for lithium–sulfur batteries. The morphology, structure and composition of the obtained NUCNT/S electrode were studied. Meanwhile, the effect of nitrogen doping on the electrochemical performance of the NUCNT/S cathode was discussed in detail. The results show that the NUCNT/S cathode presents excellent cyclability and rate capability, and the superior electrochemical properties of the NUCNT/S cathode can be attributed to the co-effect of rational design of the cathode nanostructure and successful nitrogen doping in the carbon matrix. On the one hand, NUCNTs with large surface areas and a special unzipped structure have a good effect on wrapping S particles. On the other hand, N doping can not only promote the distribution of sulfur particles and the electronic conductivity of the carbon matrix, but also immobilize the sulfur particles and polysulfides, which results in good sulfur utilization and long cycle life of the cathode. Therefore, the design of the NUCNT/S composite provides a promising candidate for the cathode material for lithium–sulfur batteries, and it also offers a strategy to prepare a sulfur cathode with a novel structure and advanced performance.